Improvement of State-Administrative Practice by Means of Career Consulting (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article considers the issues of improving the state-management practice by means of career consulting. It is determined that at the present stage, in the context of the implementation of the administrative reform in Ukraine, whose objective is to directly enhance the effectiveness of the existing public administration system in the state, priority is given to the modernization of the civil service, of which the systematic improvement of the professional level of personnel for work in public administration throughout the entire period of work. It is determined that the modern model of professional training of civil servants is mostly informational and / or academic in nature and is less characterized by dynamism and practical purposefulness in obtaining empirical knowledge, certain competences and skills necessary for fulfilling the functional duties. In this article it is proved that career counseling is a rather important resource for the professional development of the personality of civil servants. Also, within the framework of the research problems, it is proposed to study the factors influencing career development in order to increase the effectiveness of consulting activities. Given that these factors are not only personal, psychological, but also situational in nature, emphasis is placed on the need for a consistent study of the emergence of new socio-political and economic conditions that arise in society and their reflection in the self-awareness of employees. Without this, it has been proved that it is impossible to help specialists form a consciously adequate choice of the direction of professional development and on this basis an effective variant of building a professional career. Given the data we have received, we note that the tasks of career counseling are the acquisition of management skills by employees, or, more precisely, the ability to set and achieve goals based on the needs of clients (visitors to the civil service). As a result of this study, a combination of career orientations has been discovered, which clearly needs strengthening skills to manage one's state. As an output, the opportunity is justified, through career counseling, to develop the professionalism of the employee through training in self-regulation and the elimination of anxiety reactions.
Keywords: state-administrative practice, career, consulting